(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Branding of a product or service ensures legal protectionfor the brand name and offers differentiation in comparison to the competitors‘offering in the market place. In markets where competition is rare, goods canbe sold as commodities and the name of the maker may not matter much. Howeversituation is different in highly competitive markets, where competitors arevying for the attention of customers with similar product offerings and it isdifficult to create product differentiation.